Pelatihan Pembuatan Camilan sebagai Edukasi Kesehatan Pangan Keluarga di Blang Nangka Kecamatan Blangjerango Kabupaten Gayo Lues - Hayati, Rita; Marliah, Ainun; Nurahmi, Erida; Hasanuddin (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2023)
This activity was carried out to help with the problems faced by the partner group, namely housewives in Blang Nangka Village, Blangjeurango District, Gayo Lues Regency. The aim of the activity is to understand the importance of healthy family food for the mothers who are members through education and strengthening the motivation of the mothers to prepare their own healthy snacks for the family through demonstrations and practice of making snacks. The method used to achieve the goal is to carry out community service activities. Education through lectures and questions and answers is used to explain family food health material, while demonstrations and practice are carried out in training on making the healthy snack risol. In general, the results achieved by community service activities are participant satisfaction reaching 100%. Analysis of activity participant satisfaction questionnaires generally indicates that the activity was successfully implemented. Community service activities carried out with partner groups of housewives in Blang Nangka Village, Blangjeurango District, Gayo Lues Regency were well received by the participants. The aim of the activity can be achieved by participants understanding the health of family food. Apart from that, participants were also motivated to make their own snacks for their family members and carry out this service activity to groups of mothers next to the village of this service activity.